Corporate Governance Dan Karakteristik Perusahaan Sebagai Determinan Kinerja Keuangan Perusahaan - Junianto, Setiawan Fathoni (JIFA (Journal of Islamic Finance and Accounting), 2018)
The objectives of this research is to investigate the relationship between board of commissioners, independent board of commissioners, amount of board commissioners meeting, firm size and firm age in the financial performance of manufacturing industry in Indonesian stock exchange period 2016. Sampel in this study using purposive sampling as many as 94 companies in Indonesia. The results shows that proportion of independent board of commissioners and firm age have significant effect on the companys financial performance. Then board of commissioners, amount of board of commissioners meeting and firm size have no significant effect on financial performanceKeywords: GCG, Firm characteristic, financial performance